Simulation of Groundwater Flow, Denpasar-Tabanan Groundwater Basin, Bali Province - Tirtomihardjo, Heryadi; Setiawan, T. (Geological Agency, 2011)
DOI:Â 10.17014/ijog.v6i3.123Due to the complex structure of the aquifer systems and its hydrogeological units related with the space in which groundwater occurs, groundwater flows were calculated in three-dimensional method (3D Calculation). The geometrical descritization and iteration procedures were based on an integrated finite difference method. In this paper, all figures and graphs represent the results of the calibrated model. Hence, the model results were simulated by using the actual input data which were calibrated during theÂ simulation runs. Groundwater flow simulation of the model area of the Denpasar-Tabanan Groundwater Basin (Denpasar-Tabanan GB) comprises steady state run, transient runs using groundwater abstraction in the period of 1989 (Qabs-1989) and period of 2009 (Qabs-2009), and prognosis run as well. Simulation results show, in general, the differences of calculated groundwater heads and observed groundwater heads at steady and transient states (Qabs-1989 and Qabs-2009) are relatively small. So, the groundwater heads situation simulated by the prognosis run (scenario Qabs-2012) are considerably valid and can properly beÂ used for controlling the plan of groundwater utilization in Denpasar-Tabanan GB.